Influencia del cambio en el régimen de flujo de agua en el comportamiento dinámico de laderas (2015)
The present work corresponds to the research carried out on the dynamic behavior of slopes before the change in the flow regime applied on a natural slope called Taco 3. Taco 3 has aroused the interest of several investigations, since it corresponds to a mega-slip which involved the movement of 3.2 million volume of land, product of seismic movements recorded on May 22, 1960 (Mw = 9.5) in the vicinity of Valdivia, Chile. The research is divided into two main parts: The first is based on determining the factors that led to the slide of Taco 3 and the second is studying the influence that would have a sudden increase in the normal levels of the San Pedro River on the stability of the Taco 3 in its current condition. For the analysis of the dynamic behavior of the slope, stability analysis was carried out by the methods of limit equilibrium and finite elements, flow analysis, stress and strain analysis, and dynamic analysis.